2013
DOI: 10.3892/ol.2013.1399
|View full text |Cite
|
Sign up to set email alerts
|

Matrine effectively inhibits the proliferation of breast cancer cells through a mechanism related to the NF-κB signaling pathway

Abstract: Matrine is an alkaloid isolated from Sophora flavescens. The present study aimed to determine whether matrine effectively inhibits the proliferation of breast cancer cells, and the underlying mechanism(s) of its antitumor function. The effects of matrine on the cell viability of ER-positive MCF7 cells, HER2-positive BT-474 cells and highly metastatic MDA-MB-231 cells were measured using MTT and apoptosis assays. Western blot analysis was performed to investigate the expression levels of the inhibitor of κB (Iκ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…Breast cancer was the second leading cause of cancer related death among women worldwide. Although concerted efforts have been made in breast cancer therapy, it is still estimated that over 1,000,000 women are newly diagnosed with breast cancer every year worldwide and that more than 400,000 cases will die from breast cancer (Li et al, ; Shao et al, ; Li et al, ). Matrine was reported to effectively inhibit the proliferation of breast cancer cells, including endoplasmic reticulum (ER)‐positive Michigan Cancer Foundation (MCF) cells, HER2‐positive BT‐474 cells, and highly metastatic MDA‐MB‐231cells.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer was the second leading cause of cancer related death among women worldwide. Although concerted efforts have been made in breast cancer therapy, it is still estimated that over 1,000,000 women are newly diagnosed with breast cancer every year worldwide and that more than 400,000 cases will die from breast cancer (Li et al, ; Shao et al, ; Li et al, ). Matrine was reported to effectively inhibit the proliferation of breast cancer cells, including endoplasmic reticulum (ER)‐positive Michigan Cancer Foundation (MCF) cells, HER2‐positive BT‐474 cells, and highly metastatic MDA‐MB‐231cells.…”
Section: Introductionmentioning
confidence: 99%
“…The death of cancer cells was observed in the matrine treatment group. The expression of the inhibitor of κB (IκB) kinase β (IKKβ) was downregulated by matrine in the NF-κB signaling pathway [12] . Another study indicated that matrine might suppress breast cancer cell (MCF-7) growth by inducing apoptosis and cell cycle arrest at the G 1 /S phase in a dose-and time-dependent manner via the miR-21/PTEN/Akt pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Matrine exerts several therapeutic effects on cancer cells, including antiangiogenic effects, antiproliferation, cellcycle blockage, and induction of cell apoptosis [26][27][28][29][30], but its antimetastatic effects in osteosarcoma remain unclear. Thus, in this study, we intended to verify whether a low concentration level of matrine exerted anti-invasion effects in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%